Sexual Risk, Substance Use and Undiagnosed Seropositivity among Men Who Have Sex with Men and Women in Miami, Florida - David W. Forrest; Gabriel Cardenas; Lisa R. Metsch; Charlene S. Dodson; Marlene LaLota (University of North Florida, 2015)
This paper utilizes the National HIV Behavioral Surveillance data in Miami for the men who have sex with men cycle (NHBS-MSM2) in 2008. We analyzed sexual risk, substance use and undiagnosed seropositivity in a diverse sample of men who have sex with men and women (MSMW) and compared them with MSM. Of 152 MSMW, 15.1% tested HIV positive with 73.9% previously undiagnosed. Almost half (44.1%) of the MSMW reported unprotected sex with male and female partners in the past year. More MSMW than MSM had undiagnosed HIV infection, exchanged sex for money or drugs, used crack and cocaine, been high during sex, and had not received HIV treatment if HIV positive. Undiagnosed HIV infection among MSMW was associated with Black race, older age, non-alcohol use and Ecstasy use. Our findings indicate that MSMW represent a unique population at risk of acquiring and transmitting HIV in Miami.